2021
DOI: 10.2196/23302
|View full text |Cite
|
Sign up to set email alerts
|

Tabletop Board Game Elements and Gamification Interventions for Health Behavior Change: Realist Review and Proposal of a Game Design Framework

Abstract: Background Games, when used as interventional tools, can influence behavior change by incentivizing, reinforcing, educating, providing feedback loops, prompting, persuading, or providing meaning, fun, and community. However, not all game elements will appeal to all consumers equally, and different elements might work for different people and in different contexts. Objective The aim of this study was to conduct a realist review of tabletop games targetin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 53 publications
0
34
0
1
Order By: Relevance
“…To disseminate COVID-19 prevention messages in an original and engaging way, a transdepartmental and multidisciplinary development team created Escape COVID-19 [ 24 ], a serious game based on Nicholson’s concept for meaningful gamification [ 25 ]. By increasing the players’ engagement, serious games, which also enhance knowledge, satisfaction, and skills [ 26 ], can help promote adequate behaviors [ 27 , 28 ]. The impact of Escape COVID-19 was assessed in a population of nursing home employees [ 29 ]: In a triple-blind controlled trial, the self-reported likelihood of changing infection prevention and control practices was almost 4 times higher in the group of participants who had followed the serious game [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…To disseminate COVID-19 prevention messages in an original and engaging way, a transdepartmental and multidisciplinary development team created Escape COVID-19 [ 24 ], a serious game based on Nicholson’s concept for meaningful gamification [ 25 ]. By increasing the players’ engagement, serious games, which also enhance knowledge, satisfaction, and skills [ 26 ], can help promote adequate behaviors [ 27 , 28 ]. The impact of Escape COVID-19 was assessed in a population of nursing home employees [ 29 ]: In a triple-blind controlled trial, the self-reported likelihood of changing infection prevention and control practices was almost 4 times higher in the group of participants who had followed the serious game [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The near-universal household penetration of digital games may result in physical play activities, such as board games and other tabletop games, being perceived as old-fashioned [ 24 ]. The digital aspects of such games include advantageous features, such as game analytics or, in the case of education, learning analytics [ 25 , 26 ]; ease of upscaling or mass deployment [ 27 ]; and ease of modification without the need to physically produce new materials [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its success is largely dependent on eliciting a playful, enjoyable, fun experience while simultaneously delivering efficacious behavior change techniques (BCTs) [ 1 ]. Gs4H seem to effect change in various contexts [ 2 - 5 ]. However, existing studies provide limited guidance for developers interested in designing novel Gs4H.…”
Section: Introductionmentioning
confidence: 99%